Acute haemodynamic comparison of amrinone and pirbuterol in chronic heart failure. Additional effects of isosorbide dinitrate. Issue 3 (March 1983) - Bayliss, J; Norell, M; Canepa-Anson, R; Reuben, S R; Poole-Wilson, P A; Sutton, G C
Abstract : A randomised, within patient comparison was made in patients with severe chronic heart failure, to study the acute haemodynamic effects of oral agents which have inotropic and vasodilator properties. A non-glycosidic non-adrenergic positive inotropic agent with vasodilator properties (amrinone) was compared with a beta-agonist which has vasodilator and positive inotropic effects (pirbuterol). To assess whether combined treatment with a venodilator might be advantageous, the effect of adding isosorbide dinitrate was studied. Oral amrinone or pirbuterol were given in random order to each of 13 patients, on successive days, and oral isosorbide dinitrate was added after two-and-a-half hours. Control values before amrinone or pirbuterol were similar, and both drugs increased cardiac index while reducing left ventricular filling pressure, right atrial pressure, and systemic vascular resistance. Heart rate and blood pressure were unchanged. The magnitude of the changes caused by amrinone and pirbuterol were not significantly different. The addition of isosorbide dinitrate caused further falls in left ventricular filling pressure and right atrial pressures, and a fall in heart rate with each drug. Other measurements remained unchanged. Although amrinone and pirbuterol have different pharmacological properties, their acute haemodynamic effects in patients with chronic heart failure are indistinguishable.